Understanding Student Experiences and Interaction in Virtual Learning Environments: Evidence from Resource-Constrained Universities in Latin America - Mamani-Flores, Adderly; et al., (European Journal of Social Science Education and Research, 2026)
Virtual Learning Environments (VLEs) have become central to higher education, yet student experiences in resource-constrained settings remain insufficiently explored. This study examines perceptions, usage patterns, and satisfaction with VLEs among Social Sciences students at Peru’s National University of the Altiplano (UNA). A quantitative, cross-sectional design was employed using a stratified random sample of 112 undergraduates (semesters 4–8), analyzed through descriptive and correlational statistics. Results show that 57.1% of students reported positive experiences, particularly valuing access to learning materials and student–instructor interaction. However, significant challenges persist: 50.9% encountered recurrent technical problems, and 38.4% perceived VLEs as less effective than face-to-face instruction. Videoconferencing tools, mainly Zoom and Google Meet, dominated instructional delivery, while gaps in personalized support and technical assistance were evident. Overall, the findings suggest that although VLEs are perceived as valuable, their effectiveness is constrained by limited digital training and interaction design. Targeted institutional interventions are recommended to enhance VLE performance in underserved higher education contexts.
Keywords: Virtual learning environments, higher education, student perceptions, digital inequality, student experience.